Dysfunctional Inhibitory Mechanisms in Locus Coeruleus Neurons of the Wistar Kyoto Rat - Bruzos-Cidón, C (Int J Neuropsychopharmacol, 2015)
BACKGROUND: The noradrenergic nucleus locus coeruleus (LC) has functional relevance in several psychopathologies such as stress, anxiety, and depression. In addition to glutamatergic and GABAergic synaptic inputs, the activation of somatodendritic α(2)-adrenoceptors is the main responsible for LC activity regulation. The Wistar Kyoto (WKY) rat exhibits depressive- and anxiety-like behaviors and hyperresponse to stressors. Thus, the goal of the present study was to investigate in vitro the sensitivity of α(2)-adrenoceptors, as well as the glutamatergic and GABAergic synaptic activity on LC neurons of the WKY strain. METHODS: For that purpose patch-clamp whole-cell recordings were done in LC slices. RESULTS: The α(2)-adrenoceptors of LC neurons from WKY rats were less sensitive to the effect induced by the agonist UK 14 304 as compared to that recorded in the Wistar (Wis) control strain. In addition, the GABAergic input to LC neurons of WKY rats was significantly modified compared to that in Wis rats, since the amplitude of spontaneous GABAergic postsynaptic currents was reduced and the half-width increased. On the contrary, no significant alterations were detected regarding glutamatergic input to LC neurons between rat strains. CONCLUSIONS: These results point out that in WKY rats the inhibitory control exerted by α(2)-adrenoceptors and GABAergic input onto LC neurons is dysregulated. Overall, this study supports in this animal model the hypothesis that claims an imbalance between the glutamatergic-GABAergic systems as a key factor in the pathophysiology of depression.